Our C-Arm-Free Minimally Invasive Technique for Spinal Surgery: The Thoracolumbar and Lumbar Spine—Based on Our Experiences - Konstantinos Zygogiannis; Masato Tanaka; Naveen Sake; Shinya Arataki; Yoshihiro Fujiwara; Takuya Taoka; Koji Uotani; Abd El Kader Al Askar; Ioannis Chatzikomninos (Medicina, 2023)
Background and Objectives: The implementation of intraoperative imaging in the procedures performed under the guidance of the same finds its history dating back to the early 1990s. This practice was abandoned due to many deficits and practicality. Later, fluoroscopy-dependent techniques were developed and have been used even in the present time, albeit with several disadvantages. With the recent advancement of several complex surgical techniques, which demand higher accuracy and are in conjunction with the existence of radiation exposure hazard, C-arm-free techniques were introduced. In this review study, we aim to demonstrate the various types of these techniques performed in our hospital. Materials and Methods: We have retrospectively analyzed and collected imaging data of C-arm-free, minimally invasive techniques performed in our hospital. The basic steps of the procedures are described, following with a discussion, along with the literature of findings, enlisting the merits and demerits. Results: MIS techniques of the thoracolumbar and lumbar spine that do not require the use of the C-arm can offer excellent results with high precision. However, several disadvantages may prevail in certain circumstances such as the navigation accuracy problem where in the possibility of perioperative complications comes a high morbidity rate. Conclusions: The accustomedness of performing these techniques requires a steep learning curve. The increase in accuracy and the decrease in radiation exposure in complex spinal surgery can overcome the burden hazards and can prove to be cost-effective.